ANALISIS KINERJA KEUANGAN PADA PT GUDANG GARAM, TBK - Huntojungo, Febriani; Ferdinand Runtuwene, Roy; Keles, Dantje (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
Summary. The performance of the company's financial statements stable financial condition is seen in 2014 sales increased from year to year, ranging from 65% in 2012 to 66.8% in 2013 and reached 68% in 2014. While in 2015 Sales decreased Each by 0.5% to 60.9 billion cigarettes. The main question in this study is "How Financial Performance Analysis at PT Gudang Garam?". This study aims to determine the financial performance at PT. Gudang Garam Tbk period of 2011 to 2015. According Munawir (2002), financial statements is one of the financial information sourced from internal companies concerned. Financial statements. Company performance is a description of the financial position of a company that is analyzed with the tools of financial analysis, so it can be known about the good financial situation of a company. To analyze the financial statements, then one method. The visual ratio of a relationship or balance (mathematical relationship) between a certain amount to another amount. The types of financial ratios used are: Liquidity Ratio, Solvency Ratio, Rentability Ratio. Based on the results of financial ratio analysis. Ratios, ratios and ratios of profitability indicate the company's financial performance is in good condition. Fluctuate. The results of the company's performance. On ratio. Solvency ratios and ratios. When the profitability ratio shows a result that has not been maximized. Then it can be concluded the financial condition of the company PT. Gudang Garam Tbk is in good condition. In this case the company must be able to maintain good financial performance that is liquidity, solvency and profitability. Keywords: Performance Analysis, Liquidity, Solvency, Profitability.